Factors affecting survival of women with breast cancer in King Fahad Medical City, Saudi Arabia - Abu Zaid, Lamyaa Z.; Nuzhat, Ayesha; Rafiqe, Munazzah (International Journal Of Community Medicine And Public Health, 2017)
Background: Breast cancer is the most frequently diagnosed cancer among women in 140 of 184 countries worldwide. The association between breast cancer survival and socio-demographic and pathologic factors has been widely studied in the developed countries. But scarce data is available from Saudi Arabia. We aimed to determine the overall observed one year and three years survival rate of female breast cancer patients and to investigate the factors affecting survival rate. Methods: Retrospective data was collected from the cancer center registry at King Fahad Medical City (KFMC) that included all women diagnosed with breast cancer between 1st January 2011 till 31st December 2012 and were followed to 31st December 2015 (cut off point for follow-up). Kaplan-Meier analysis was done to assess overall survival. The factors affecting survival rate such as age, histological type, tumor grade at diagnosis, metastases and treatment options were investigated using log rank test and Cox regression analysis. Results: The overall observed survival probability of the study population at 1, and 3 years was 95%, and 85%, respectively. The 3 year survivals for the younger (≤40 years), 41-50 years and older (50+ years) patients were 83.9%, 90.6% and 80.6% respectively, the differences not reaching statistical significance. There were statistically significant associations between three year survival and histological type of tumour, laterality, metastases and type of treatment by the univariate analysis log rank test. Conclusions: One and three-year survival rate of breast cancer at KFMC was 96% and 85% respectively. Investigating the factors affecting survival rate is one of the most essential means of improving cancer prognosis.